The Influence of Profitability, Sales Growth, and Firm Size on Firm Value in The Consumer Non-Cyclicals - Nugraha, Ivonne Christabella; Indah, Nopiani; Budianto, Hendy (Proceedings International Conference on Education Innovation and Social Science, 2025)
This study aims to analyze the effect of profitability on firm value, the effect of sales growth on firm value, and the effect of firm size on firm value. The research was conducted during 2019-2024. The population in this study consists of 131 companies in the non-cyclical industrial sector listed on the Indonesia Stock Exchange, with a sample of 78 companies. The sampling technique used is purposive sampling. Data processing was carried out using Statistical Product and Service Solution (SPSS) version 26. The results show that profitability has a positive effect on firm value. However, sales growth and firm size have no effect on firm value.